An inquiry into the digitisation of border and migration management: performativity, contestation and heterogeneous engineering. Issue 1 (2nd January 2021) - Glouftsios, Georgios; Scheel, Stephan
Abstract: This article is concerned with the digitisation of border security and migration management. Illustrated through an encounter between a migrant and the Visa Information System (VIS) – one of the largest migration-related biometric databases worldwide – the article's first part outlines three implications of digitisation. We argue that the VIS assembles a set of previously unconnected state authorities into a group of end users who enact border security and migration management through the gathering, processing and sharing of data; facilitates the practice of traceability, understood as a rationality of mobility control; and has restrictive effects on migrants' capacity to manoeuvre and resist control. Given these implications, the article's second part introduces three analytical sensitivities that help to avoid some analytical traps when studying digitisation processes. These sensitivities take their cue from insights and concepts in science and technology studies (STS), specifically material semiotics/ANT approaches. They concern, firstly, the ways that data-based security practices perform the identities of the individuals that they target; secondly, the need to consider possible practices of subversion by migrants to avoid control-biased analyses; and finally, the challenge to study the design and development of border security technologies without falling into either technological or socio-political determinism.